2017
DOI: 10.1002/lite.201700009
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic applications for emu oil

Abstract: Summary Emu oil is a rich source of fatty acids extracted from the subcutaneous and retroperitoneal fat of the Emu (a flightless bird native to Australia). Indigenous Australian people first used emu oil for its healing and pain‐alleviation properties. Currently, emu oil is commercially available for topical and oral administration, marketed as an anti‐inflammatory and antioxidant formulation with reparative properties. A limited number of clinical trials have shown indications of efficacy for topically‐applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
2
Order By: Relevance
“…2006]. Hodowle emu zlokalizowane są zarówno w Australii, jak i w różnych częściach świata [Sales 2007, Mashtoub 2017. Szacuje się, że tylko w Indiach całkowita populacja emu liczy 1,4 miliona [Warale i in.…”
Section: Występowanie I Hodowla Emuunclassified
See 1 more Smart Citation
“…2006]. Hodowle emu zlokalizowane są zarówno w Australii, jak i w różnych częściach świata [Sales 2007, Mashtoub 2017. Szacuje się, że tylko w Indiach całkowita populacja emu liczy 1,4 miliona [Warale i in.…”
Section: Występowanie I Hodowla Emuunclassified
“…Ma właściwości antyoksydacyjne i pochłaniające wolne rodniki [Snowden i Whitehouse 1997, Jeengar i in. 2015, Mashtoub 2017. Dodatkowo działa jak naturalny filtr UV [Patel i in.…”
Section: Tłuszcz Emu -Remedium Na Liczne Problemyunclassified
“…Topical application of emu oil has been shown to reduce in ammation associated with reduced levels of interleukin 1-alpha (IL-1α), tumor necrosis factor-alpha (TNFα) and other proin ammatory cytokines in a croton-oil-induced in ammation mouse model [6,7]. More recently, well-controlled pre-clinical studies have demonstrated the e cacy of orallyadministered emu oil in attenuating in ammatory intestinal disorders [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcers (PPU) can be presented at any age; however, it predominates in childhood, being more frequent before 5 years of age and persists in adulthood in up to 60-70% of patients [5]. Emu oil is known for the use that the natives of Australia gave it as a remedy to alleviate different ailments for 200 years [6]. In the First World War, ozonated oils were used for therapeutic purposes, as well as the healing of wounds and fissures [7].…”
Section: Introductionmentioning
confidence: 99%